1996
DOI: 10.1063/1.868937
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of near-interface turbulence in coupled gas-liquid flow

Abstract: Turbulence structures near the interface between two flowing fluids have been resolved by direct numerical simulation. As a first step the interface has been kept flat, corresponding closely to the recent gas-liquid flow experiments of Rashidi and Banerjee [Phys. Fluids A 2, 1827 (1990)], with the fluids coupled through continuity of velocity and shear stress boundary conditions. For density ratios between the fluids typical of air and water, the turbulence characteristics on the gas side are quite similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
80
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 25 publications
17
80
2
Order By: Relevance
“…Alternatively, there have been relatively few DNS-based studies of turbulence in problems involving two-phase flows, if one excludes earlier research focusing on freesurface turbulence with and without wind shear (Lam & Banerjee 1992;Komori et al 1993b;Lombardi, DeAngelis & Banerjee 1996). Because of its relative simplicity, stratified gas-liquid flow has been the configuration best suited to investigating the underlying physics of turbulence at the interface.…”
Section: Wave Breaking and Turbulencementioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, there have been relatively few DNS-based studies of turbulence in problems involving two-phase flows, if one excludes earlier research focusing on freesurface turbulence with and without wind shear (Lam & Banerjee 1992;Komori et al 1993b;Lombardi, DeAngelis & Banerjee 1996). Because of its relative simplicity, stratified gas-liquid flow has been the configuration best suited to investigating the underlying physics of turbulence at the interface.…”
Section: Wave Breaking and Turbulencementioning
confidence: 99%
“…The authors found that the lighter phase might look at the interface like a solid surface. Fulgosi et al (2003) extended the research of Lombardi et al (1996) to non-flat, sheared interfaces by considering stratified flow with a freely deformable interface in the gravity-capillary wave regime. With regard to wave breaking, multiple contributions have been made using LES (Christensen 2006;Lubin et al 2006).…”
Section: Wave Breaking and Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…Unsteady RANS and LES approaches were used by Wegner et al 21,22 to simulate unconfined swirling flow and spiral/helical vortical structures were obtained. DNS has been used to simulate the interface changes and turbulence in two-phase environments [23][24][25] but the two phases were divided into two single-phase subdomains while the gas flow was considered to be incompressible. Klein 26 performed DNS of a liquid sheet exhausting into a gaseous incompressible atmosphere under moderate Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a better understanding of turbulence near deformable interfaces has been a long standing research challenge, and experiments and numerical simulations have already revealed many important aspects of the structure of the interface and the adjacent turbulence (e.g., Lugt and Ohring, 1992;Tsai, 1996;Lombardi et al, 1996;Fulgosi et al, 2003;Guo and Chen, 2010). The interfacial fluctuations respond to the turbulent kinetic energy, length scales and vortex structures in the fluids adjacent to the interface (e.g., Rein, 1998;Smolentsev and Miraghaie, 2005) and the turbulence is affected by the interfacial properties (elasticity, viscosity and energy), posing a twoway interface-turbulence coupling.…”
mentioning
confidence: 99%